Integrated heterogeneous database of membrane protein for protein-protein interactions (PPIs) identification / Winddy Pindah - Pindah, Winddy (2012)
More than 50% of currently market drug target are from membrane protein. As consequence, both academia and industry targeting membrane protein to be as subject of intense for drug discovery. In order to discover target from membrane protein effectively, researcher need to predict the membrane protein-protein interactions (PPIs). Knowledge of PPIs promising new approach to discover drug by targeting the undruggable fragment based. However, to facilitate this task is not easy as their estimation due to the biophysical properties of membrane protein. There are several study have been done to improve PPIs identification in membrane protein, among the solution is incorporating various biologically meaningful data such as network topological features, protein primary sequences and structures. Thus, the objectives of this study are to design an integrated heterogeneous database of membrane protein from Protein Data Bank (PDB), Protein Topology Graph Library (PTGL) and Universal Protein Resource (Uniprot) and to use data from an integrated heterogeneous database of membrane protein resources for membrane proteinprotein interactions (PPIs) identification. Most of information gathered on this study obtained from interview and review to previous related study. This study aims to contribute to development and improvement of technology or tools to study membrane proteins as the important resource for drug target, in order to improve or develop novel pharmacological drug targets.